On the UV-light-induced Desorption/Adsorption Mechanism of Atmospheric Species in Solution-processed Zinc Oxide Thin Films - Cantuária, José Bruno [UNESP]; Gozzi, Giovani [UNESP]; Santos, Lucas Fugikawa [UNESP] (Springer Nature, 2019)
Zinc oxide (ZnO) is a n-type transparent semiconductor which can be processed by low cost techniques (such as spray-pyrolysis and spin-coating) and can be applied as the active layer of thin-films transistors (TFTs). The electrical properties of ZnO films are strongly affected when the device is exposed to room conditions and/or UV-light, suggesting possible applications as UV or/and gas sensors. Atmospheric oxygen molecules adsorbed on ZnO surface act as charge traps, decreasing the material conductivity. The incidence of UV-light causes an increase of the material conductivity due to the photogeneration of electron-hole pairs via direct band-to-band transitions (classic photoconductivity process) and due to the desorption of oxygen molecules, which presents a relatively slower response and is a less understood mechanism. In the current paper, we study the influence of environmental parameters, such as temperature, humidity and UV-light intensity, on the electrical properties of spin-coated ZnO thin films to understand the role of the desorption mechanism on the photoconductivity process. The analysis of the device current vs. time curves shows the existence of two light-induced desorption mechanisms: i) one which increases the electrical conductivity of the ZnO film (desorption-like process) and ii) a second one which decreases the conductivity (adsorption-like process). A Plackett-Burman design of experiment (DOE) was used to study the influence of characterization factors like UV intensity, temperature and humidity on electrical parameters obtained from the experimental curves. We observed that the desorption-like process is a first order mechanism, exhibiting desorption rate proportional to n(t), where n(t) represents the adsorbate concentration as a function of the time, whereas the adsorption-like mechanism exhibits a desorption rate proportional to the forth power of n(t).
Keywords: adsorption; electrical properties; semiconducting; thin film